Dental Undergraduates and Interns’ Awareness, Attitudes, and Perception of Radiological Protection - Elfatih Abuelhia; Ali Alghamdi; Abdulrahman Tajaldeen; Osama Mabrouk; Adel Bakheet; Haney Alsaleem; Wejdan Alaraik; Amir MSmar; Faisal Quwaihes; Khaled Alshahrani; Yahya Hlosh; Salem Alghamdi; et al. (International Journal of Dentistry)
Medical ionizing radiation is widely used in hospitals, in particular dental clinics, and in medical research to facilitate the diagnosis and treatment of patients. The awareness, attitude, and perception of ionizing radiation exposure among dental undergraduate students and interns in radiological investigations and dental care clinics were investigated. A cross-sectional study was conducted; 17 questions were designed online using the software “QuestionPro,” which was licensed to the University of Imam Abdulrahman Bin Faisal. Participants included senior medical dental students from Imam Abdulrahman Bin Faisal University in their third to fifth years, as well as interns from King Fahad University Hospital and private dental care clinics. A total of 855 participants viewed, 360 started the questionnaire, and 258 (72%) completed it online. Overall, knowledge was lacking; 32% of respondents incorrectly believed that magnetic resonance imaging and ultrasound used ionizing radiation, while 38% were unsure. Dental X-rays were deemed harmful by 40% (n = 104) of respondents. According to 33% (n = 85) of participants, there is no radiation scatter during an X-ray or CT scan, while 30% (n = 76) are unsure. Respondents (44%; n = 104) were unaware of the radiation dose from a chest radiograph and (45%; n = 116) overestimated the radiation dose. The effects of ionizing radiation on healthy tissue are known to more than half of the participants (54%). According to 39% of respondents, digital radiography exposes them to less radiation than traditional radiography. In terms of radiation protection and hazard, 46% said personal monitoring badges should be always worn and 58% (n = 150) said lead aprons should be used on a regular basis. 63% of the subjects had received radiation protection education, such as formal lectures, tutorials, or workshops, while 37% (n = 95) had not. 53% of the respondents were not aware of the international recommendations from the International Commission on Radiological Protection. When asked if they would follow radiation protection protocols if they opened a private dental clinical practice in the future, 50% (n = 129) said they would.